THE EFFECT OF DEMONSTRATION METHOD ON WRITING PROCEDURE TEXT AT SENIOR HIGH SCHOOL - Abdullah Farih (JEELL (Journal of English Education, Linguistics and Literature) English Departement of STKIP PGRI Jombang, 2023)
This research was conducted in order to find out the effect of demonstration method on writing procedure text at eleventh grade of SMA Negeri 1 Kembangbahu.This research used a quantitative design. In collecting data, the researcher used experimental research. The researcher used quasi-experimental research. There were involved two classes for the research, namely experiment class and control class. The researcher used ttest to calculate the data. The finding of the research indicated the implementation of demonstration method on writing procedure text was effective. It could be know from the result of calculation that the students gained scores between pre-test and post-test in experiment class was higher than control class. The gained scores of experiment class is 15.25. Meanwhile, the gained scores of control class is 8. Furthermore, based on statistical calculation with the significant 5%. It showed that ttest is higher than t table that was 3.98 ≥ 2.02. Therefore H0 is rejected and the Ha is accepted. It can be conclude that using Demonstration method on writing procedure text is success.